2009
DOI: 10.1016/s0828-282x(09)70120-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operator and institutional volume on clinical outcomes after percutaneous coronary interventions performed in Canada and the United States: A brief report from the Enhanced Suppression of the Platelet glycoprotein IIb/IIIa Receptor with Integrilin Therapy (ESPRIT) study

Abstract: BACKGROUND:The Enhanced Suppression of the Platelet glycoprotein IIb/IIIa Receptor with Integrilin Therapy (ESPRIT) trial compared the use of eptifibatide with placebo in 2064 coronary intervention patients. It was previously reported that Canadian patients had reduced rates of 30-day and one-year death, myocardial infarction (MI) or targetvessel revascularization (TVR) compared with patients in the United States (US). OBJECTIVE: To examine whether operator or institutional volume differences explain the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The relationship of these outcomes and operator or institutional volume has not been shown earlier. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]35 Our study demonstrates a statistically significant inverse association between operator volume and outcome (in-hospital mortality and peri-procedural complications) in the current practice. Our results are in agreement with results from previous studies done both in the percutaneous transluminal coronary angioplasty and the stent era.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The relationship of these outcomes and operator or institutional volume has not been shown earlier. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]35 Our study demonstrates a statistically significant inverse association between operator volume and outcome (in-hospital mortality and peri-procedural complications) in the current practice. Our results are in agreement with results from previous studies done both in the percutaneous transluminal coronary angioplasty and the stent era.…”
Section: Discussionmentioning
confidence: 58%
“…Our results are in agreement with results from previous studies done both in the percutaneous transluminal coronary angioplasty and the stent era. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]35,36 Previous studies have been limited by the number of centers, 12,20 state-based registry data, 8,14,15,18 inclusion of only limited cohorts, 16 lower sample size, 8,9,[11][12][13][14][15][16][17][18]20 foreign studies, 11,19,21 and most importantly they lack data from recent era. 6,7,9,16 Previous studies, which have shown a decrease in mortality with increasing operator volume, have failed to reach statistical significance because of low sample size, large confidence interval, or low procedure related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations